2011
DOI: 10.1016/j.apsusc.2011.02.081
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of flower-shaped Bi2O3 superstructure by a facile template-free process

Abstract: A novel flower-shaped Bi 2 O 3 superstructure has been successfully synthesized by calcination of the precursor, which was prepared via a citric acid assisted hydrothermal process. The precursor and Bi 2 O 3 were characterized with respect to morphology, crystal structure and elemental chemical state by field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). It was shown that both the precursor and Bi 2 O 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 38 publications
(39 reference statements)
0
27
0
Order By: Relevance
“…Bismuth-based oxides with 3D hierarchical architectures have recently attracted much attention among various semiconductor photocatalysts such as Bi 2 O 3 [1], Bi 2 WO 6 [2], Bi 2 MoO 6 [3], BiOCl [4] and Bi 2 O 2 CO 3 [5] because of their valence bands hybridized by O 2p and Bi 6s [6]. Among these compounds, Bismuth subcarbonate (Bi 2 O 2 CO 3 ), as a typical member of the Aurivillius-related oxide family, is constructed by (Bi 2 O 2 ) 2+ slabs interleaved by CO 3 2− layers [7].…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth-based oxides with 3D hierarchical architectures have recently attracted much attention among various semiconductor photocatalysts such as Bi 2 O 3 [1], Bi 2 WO 6 [2], Bi 2 MoO 6 [3], BiOCl [4] and Bi 2 O 2 CO 3 [5] because of their valence bands hybridized by O 2p and Bi 6s [6]. Among these compounds, Bismuth subcarbonate (Bi 2 O 2 CO 3 ), as a typical member of the Aurivillius-related oxide family, is constructed by (Bi 2 O 2 ) 2+ slabs interleaved by CO 3 2− layers [7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high conductivity of oxygen ions, it has been taken in consideration for solid electrolite applications [3]. In manufacturing of functional materials with Bi 2 O 3 , electro-deposition, synthesis with microwave method and chemical vapor deposition method are generally used and various composite structures or semiconductive nano brillates can be succesfully produced in form of nanoparticles, nano lms or nano bers [4][5][6]. Some studies are available in production of Bi Electrospinning is an alternative method to produce functional composite structures.…”
Section: Introductionmentioning
confidence: 99%
“…Such practical research involves implementation of morphological control of Bi 2 O 3 particles as a way to improve their properties. Various shapes of Bi 2 O 3 particles have been reported, such as nanowires [2], nanorods [5] [10] [11], nanotubes [14], and flowers [1] [6] [8] [15] [16] [17]; these shapes have been reported to lend excellent properties to the particles. Works such as those outlined next have specifically reported that the flower shape of Bi 2 O 3 particles shows potential to lend excellent properties to the particles, on account of the large specific surface area in the case of this shape.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [17] synthesized flower-shaped Bi 2 (CO 3 )O 2 particles consisting of nanosheet petals in the presence of citric acid. By calcining the particles, they succeeded in converting them to flower-shaped α-Bi 2 O 3 while retaining the morphology of the Bi 2 (CO 3 )O 2 particles.…”
Section: Introductionmentioning
confidence: 99%